2000
DOI: 10.1111/j.1750-3639.2000.tb00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Astroblastoma: Clinicopathologic Features and Chromosomal Abnormalities Defined by Comparative Genomic Hybridization

Abstract: Astroblastomas are uncommon brain tumors whose classification and histogenesis have been debated. Precise criteria for diagnosis have been described only recently, but have not found wide acceptance. We report the clinical, radiographic, and histopathologic features of 20 astroblastomas, and the chromosomal alterations in seven cases as detected by comparative genomic hybridization (CGH). The tumors occurred both in children and young adults (average age, 14 years), most often as well circumscribed, peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
171
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(183 citation statements)
references
References 14 publications
(23 reference statements)
8
171
4
Order By: Relevance
“…The typical histopathological features of astroblastoma are the perivascular pseudorosette of GFAP-positive cells with short and stout cytoplasmic processes, radiating towards central blood vessels that often demonstrate sclerosis [3][4][5]. Other histological characteristics are lack of fibrillary background and compressing rather than infiltrative margin [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The typical histopathological features of astroblastoma are the perivascular pseudorosette of GFAP-positive cells with short and stout cytoplasmic processes, radiating towards central blood vessels that often demonstrate sclerosis [3][4][5]. Other histological characteristics are lack of fibrillary background and compressing rather than infiltrative margin [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Focal or multifocal regions of high cellularity, anaplastic nuclear features, elevated mitotic indices (>5 per 10 HPF), vascular proliferation and necrosis with pseudopalisading correspond to this high-grade group 4 .…”
Section: Discussionmentioning
confidence: 85%
“…Brat et al 4 , using comparative genomic hybridization, detected chromosomal abnormalities in every case studied, the gain of 20q being the most frequent. Although the spectrum of chromosomal alterations indicated that astroblastoma may have its own genetic profile, none of the detected anomalies were specific for malignancy.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, the origin of these tumors has been debated, because they share common histological characteristics with ependymomas and astrocytomas. Recent studies suggested that astroblastoma is a distinct histological and genetic entity (6,7,31,39). It has a distinctive characteristic of perivascular pseudorosettes with frequent vascular hyalinization.…”
Section: Introductionmentioning
confidence: 99%